2013
DOI: 10.1007/s10683-013-9379-3
|View full text |Cite
|
Sign up to set email alerts
|

Taking, giving, and impure altruism in dictator games

Abstract: We show that, if giving is equivalent to not taking, impure altruism could account for List's (2007) finding that the payoff to recipients in a dictator game decreases when the dictator has the option to take. We examine behavior in dictator games with different taking options but equivalent final payoff possibilities. We find that the recipients tend to earn more as the amount the dictator must take to achieve a given final payoff increases, a result consistent with the hypothesis that the cold prickle of tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 14 publications
6
36
0
Order By: Relevance
“…The results showed that less cupcakes were taken than given, which is in agreement with the results reported in the study of Korenok et al (2014), carried out in a specific distribution context. Since in the present study there was a situation involving the production of goods, it was considered that when the participants were in the position of giving the resources they felt more like the owners of the cupcakes than when they were asked to take the cupcakes, making it easier to transfer ownership of the cupcakes to the other character.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results showed that less cupcakes were taken than given, which is in agreement with the results reported in the study of Korenok et al (2014), carried out in a specific distribution context. Since in the present study there was a situation involving the production of goods, it was considered that when the participants were in the position of giving the resources they felt more like the owners of the cupcakes than when they were asked to take the cupcakes, making it easier to transfer ownership of the cupcakes to the other character.…”
Section: Discussionsupporting
confidence: 91%
“…The distribution of resources based on taking something for themselves or giving something to others can result in different distributed amounts (Korenok, Millner, & Razzolini, 2014), as shown in the results of this study. However, investigating a real situation of donation to a charity, Grossman and Eckel (2015) found no difference between these two types of distribution.…”
Section: Discussionsupporting
confidence: 52%
“…Finally, in consequence of our results one can alternatively use a giving or a taking frame in various research questions without changing the decision space—so long as the investigation is not focused on gender or the issue of taking/giving price, or the choice of the game (Korenok, Millner, and Razzolini , 2016) is absent.…”
Section: Discussionmentioning
confidence: 99%
“…The PG20 is the counterpart within the Patron Game framework of the GIVE* in [28]. 12 Reference [32] acknowledge that not giving is intrinsically different than taking and that the results in [21] cannot be rationalized by an impure altruism model.…”
Section: Warm Glow Of Giving (Impure Altruism)mentioning
confidence: 99%